Evaluation of the Feasibility and Sustainability of the Building Blitar Ministry of Environment and Forestry in Meeting Environmental Standards Based on Operational Functions - Heru Setiyo Cahyono; Ruli Saefudin; Lukman Arief; Devi Ratna Handini (DEARSIP : Journal of Architecture and Civil, 2026)
This study evaluates the functional feasibility and environmental sustainability of the KLHK Blitar Guard Post Building. The research methodology employed is qualitative descriptive, focusing on the primary document analysis of the Environmental Inspection Report, followed by an empirical comparison of field conditions against national regulatory frameworks and standards. The specific regulatory standards utilized include Government Regulation (PP) No. 16 of 2021 on Building Construction (as the basis for the Certificate of Functional Feasibility), Minister of Environment and Forestry Regulation (Permen LHK) No. 6 of 2021 regarding Hazardous Waste Management, Minister of Public Works and Housing Regulation (Permen PUPR) No. 21 of 2021 on Green Buildings, and specific technical references from Indonesian National Standards (SNI). These include SNI 03-7065-2005 for plumbing systems, SNI 03-2453-2002 for infiltration wells, SNI 03-6572-2001 for ventilation systems, and SNI 7231:2009 for noise measurement. The results indicate that the building is technically and administratively feasible. The facility has secured the SPPL document, produces no industrial hazardous waste, and possesses plumbing and drainage infrastructure that exceeds minimum standards (such as a 3,600-liter septic tank and a 12 m³ infiltration well). Although material usage is deemed safe, this research identified a methodological flaw in the previous audit regarding the incorrect use of SNI references for acoustic noise evaluation. In conclusion, the building operates in compliance with regulations, yet it requires further interventions, such as 3R-based domestic waste management and energy efficiency integration, to fully satisfy the ideal criteria of a Green Building.